Factors Influencing FinTech Adoption in Investment in Sulawesi in AI Technology - Qasabandiyah, Muhammad Kholidinna; Farida, Umi (Economics and Digital Business Review, 2025)
This study investigates the factors influencing the adoption of financial technology (FinTech) in investment, specifically focusing on the integration of artificial intelligence (AI) technology in Sulawesi, Indonesia. As FinTech continues to reshape the investment landscape, understanding the dynamics that drive or hinder its adoption is crucial for stakeholders, including investors, entrepreneurs, and policymakers. The research identifies key factors across four primary dimensions: technological, social, regulatory, and economic. Technological factors encompass the usability and accessibility of FinTech platforms, along with the role of AI in enhancing investment decision-making processes. Social factors examine the impact of financial literacy, cultural attitudes towards technology, and the willingness of individuals to embrace digital investment solutions. Regulatory frameworks are assessed for their role in creating an environment conducive to FinTech innovation while ensuring consumer protection. Economic factors are analyzed to understand how income levels, investment trends, and overall economic conditions influence individuals' engagement with FinTech-enabled investments. The findings indicate that a combination of these factors significantly affects the adoption of FinTech solutions in Sulawesi. By providing insights into the local context, this research aims to inform strategies that promote the effective use of FinTech and AI technologies in investment, ultimately fostering economic growth and financial inclusion in the region. The study concludes with recommendations for stakeholders to enhance the adoption of FinTech in investment and outlines directions for future research in this emerging field.